Study of the effect of aromatherapy sleep inducers spray - Rosnani Hasham @ Hisam, 1977-; Mohammad Roji Sarmidi; Ramlan Abd. Aziz, 1958-; Sulaiman Ngadiran; Fauziah Desa; Rosiah Rohani; Norsaupiah Sulaiman; Regional Symposium on Chemical Engineering (16th : 2002 : Selangor) (Skudai : Universiti Teknologi Malaysia, 2002)
50